Surgical Management of Delayed Brachial Plexopathy After Clavicle Nonunion. Issue 10 (October 2022) - McGillivray, Meghan K.; Doherty, Christopher; Bristol, Sean G.; Lawlor, David Kirk; Baxter, Keith A.; Lefaivre, Kelly A.
Abstract : Supplemental Digital Content is Available in the Text. Summary: Brachial plexopathy after conservative therapy or surgical treatment of clavicular fractures is an uncommon, yet serious complication that is associated with compression of the brachial plexus or the subclavian artery and vein because they traverse through the thoracic outlet. Surgical decompression of the brachial plexus is the recommended treatment if this condition is to occur. Although there are multiple reports of these cases in the literature, at present, there are no clear guidelines for their management. We are highlighting an institutional management algorithm, illustrated by a small retrospective case series, that uses a multidisciplinary approach in an effort to minimize complications associated with the management of clavicle nonunion.